2020
DOI: 10.1051/0004-6361/202039209
|View full text |Cite
|
Sign up to set email alerts
|

Effect of coronal loop structure on wave heating through phase mixing

Abstract: Context. The mechanism(s) behind coronal heating still elude(s) direct observation and modelling of viable theoretical processes and the subsequent effect on coronal structures is one of the key tools available to assess possible heating mechanisms. Wave heating via the phase mixing of magnetohydrodynamic (MHD) transverse waves has been proposed as a possible way to convert magnetic energy into thermal energy, but MHD models increasingly suggest this is not an efficient enough mechanism. Aims. We modelled heat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…This potentially rules out the energy pathway of resonant absorption to phase mixing as a viable mechanism for dissipating the kink wave energy in the quiescent corona. The numerical studies of Pagano & Moortel (2017); Pagano & De Moortel (2019); Pagano et al (2020) appear to show that phase mixing is inefficient for heating even when the rate of energy transfer is likely at its largest, i.e., under active region conditions. Moreover, the rate at which small-scales develop due to phase mixing is governed by the density gradient through the inhomogeneous boundary layer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This potentially rules out the energy pathway of resonant absorption to phase mixing as a viable mechanism for dissipating the kink wave energy in the quiescent corona. The numerical studies of Pagano & Moortel (2017); Pagano & De Moortel (2019); Pagano et al (2020) appear to show that phase mixing is inefficient for heating even when the rate of energy transfer is likely at its largest, i.e., under active region conditions. Moreover, the rate at which small-scales develop due to phase mixing is governed by the density gradient through the inhomogeneous boundary layer.…”
Section: Discussionmentioning
confidence: 99%
“…The density difference between the internal and external plasma of the coronal structures leads to a gradient in the Alfvén speed across the wave-guide boundary. The spatially-varying Alfvén frequency in the boundary layer enables phase mixing of rotational motions, which are described by Alfvén waves, and hence creates small spatial scales that eventually enables dissipation of the wave energy (e.g., Soler & Terradas 2015;Pagano & Moortel 2017;Pagano et al 2020). Moreover, a resonance is created at the locations where the Alfvén frequencies in the boundary layer match that of the global kink frequencies.…”
Section: B Wave Damping Theorymentioning
confidence: 99%
“…In addition, they found that nano-flare-like intermittent and localized heating is possible, even with just the wave heating mechanism, through collisions between counter-propagating Alfvén wave packets. Some of the other recent simulations with coronal heating in ARs include those of Berger & AsgariTarghi (2009), Antolin & Shibata (2010), Bingert & Peter (2011), AsgariTarghi & van Ballegooijen (2012), Hansteen et al (2015), Reep et al (2018), Cheung et al (2019), Guo et al (2019), Pagano et al (2020), Shi et al (2021), Breu et al (2022), andSarp Yalim et al (2023). Reviews of wave heating mechanisms, as well as recent progress in both observation and numerical models are available in Arregui (2015) and Van Doorsselaere et al (2020).…”
Section: Introductionmentioning
confidence: 99%
“…Further numerical simulations of propagating transverse waves excited by continuous boundary motions also show that wave driving can significantly disrupt a pre-existing density structure [162]. In this case, the evolution of the density profile permits wave energy dissipation over a large cross-sectional area, and not just the initial boundary of the loop.…”
Section: Propagating Wavesmentioning
confidence: 93%
“…This is a positive result in view of the criticism outlined in [163], that wave heating is not able to dissipate energy throughout the loop nor sustain the assumed density profile. However, whilst the heating in such simulations can be significant for some configurations, it has not been able to balance radiative losses in a dense flux tube [50,162], even for highly enhanced dissipation coefficients. Further, it remains unclear whether similar wave driving can support any form of density structure in a fully stratified atmosphere (e.g., [163,164]).…”
Section: Propagating Wavesmentioning
confidence: 99%